Mathematical modeling of flood management system in the city of Gdańsk, Oruński stream case study - Tomasz Kolerski; Dominika Kalinowska (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study This study analyses the efficiency of flood protection in a small urban catchment, based on a system of small reservoirs. Material and methods To assess the flood routing and surge reduction, a mathematical model of the river catchment was implemented. This was a lumped hydrological model, based on the SCS-CN method. Channel routing was performed, using kinematic wave equation. The sub-catchments have been determined based on the topographic maps and rain sewage systems. In the paper, the hydrological model of the water system of Potok Oruński (Oruński Stream) is presented with particular focus on the new and renovated retention structures. Hydrological modeling system of HEC HMS was used to simulate the catchment’s response to precipitation. Thanks to the recently established monitoring system of the Oruński Stream, it was possible to calibrate and validate the model. Single rain episode from April 2018 was used to perform model calibration, proving its high compatibility. The calibrated model was then used to reproduce the flood surge of July 2001, using historical catchment data. The peak discharge demonstrated a need for additional retention in the studied catchment. Theoretical scenarios were also modelled. The precipitation volume was calculated based on the IFS. As a worst-case scenario, the rain producing the most intense surface runoff was included. In all simulations, historical conditions as well the current state (2018) and projected further urbanisation of the catchment were taken into consideration. Results and conclusions Results of the study have shown reduction of the historical flood surge from July 2001 by nearly 60% when all existing flood protection systems were used.